Assessment of ambient benzene and environmental health impacts: A five-year study in Rayong’s pollution control Zone, Thailand - Chaiprakarn, Somboon; Kheawseema, Paphaon; Saengseedam, Panudet (Edelweiss Applied Science and Technology, 2025)
This study aimed to assess the temporal variation of ambient benzene concentrations and evaluate the potential health risks associated with long-term exposure in Rayong’s Pollution Control Zone, Thailand. Five years (2020–2024) of continuous air quality monitoring data from 11 automated stations were analyzed. Benzene concentrations and associated meteorological and air quality parameters were examined. Exposure assessment was conducted using the U.S. EPA’s ExpoFIRST v2.0 to estimate the average daily dose (ADD) and lifetime average daily dose (LADD). Health risks were quantified through lifetime cancer risk (LCR), hazard quotient (HQ), disability-adjusted life-years (DALYs), and environmental burden of disease (EBD). The mean annual benzene concentration was 2.32 µg/m3. The highest exposure risk was observed among children, with ADD and LADD ranging from 3.27×10-4 to 1.06×10-3 mg/kg-day. Estimated DALY losses ranged between 0.291 and 0.800 per 100,000 population for benzene concentrations of 1–5.5 µg/m3. The results highlight significant chronic health risks associated with benzene exposure, particularly in vulnerable populations. These findings support the need for stricter emission controls and continuous monitoring to mitigate long-term public health impacts in industrial regions.